2017
DOI: 10.1080/13548506.2017.1384844
|View full text |Cite
|
Sign up to set email alerts
|

Perceived sources and levels of stress, general self-efficacy and coping strategies in preclinical dental students

Abstract: Dental education programs are known to be highly stressful and stress can affect general health. The aims were to identify sources of stress among preclinical students and to evaluate their perceived levels of stress, self-efficacy and effective coping strategies in a private dental school. One hundred preclinical students in a Turkish private dental school were surveyed using dental environment stress (DES), perceived stress (PSS), general self-efficacy (G-SES) and brief coping scales (Brief-COPE). Age, gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 12 publications
4
46
1
1
Order By: Relevance
“…Self‐reported experience of anxiety and mental exhaustion before starting dental education was associated with being anxious after working with patients. This finding is in contrast to a study amongst pre‐clinical dental students that found no association between history of psychiatric treatment and stress, but it is in line with a study amongst clinical students that showed higher self‐efficacy amongst those who had no history of psychiatric treatment . It must be noted that the latter study requested information on more severe mental health conditions than those in our study.…”
Section: Discussionsupporting
confidence: 72%
“…Self‐reported experience of anxiety and mental exhaustion before starting dental education was associated with being anxious after working with patients. This finding is in contrast to a study amongst pre‐clinical dental students that found no association between history of psychiatric treatment and stress, but it is in line with a study amongst clinical students that showed higher self‐efficacy amongst those who had no history of psychiatric treatment . It must be noted that the latter study requested information on more severe mental health conditions than those in our study.…”
Section: Discussionsupporting
confidence: 72%
“…), which has an effect on the amount of stress experienced (Ersan et al. ). Specific coping styles (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that personality affects coping behaviour (Friedman et al 2006). Coping behaviour encompasses the way people react on a behavioural, cognitive and emotional level to situations that require adjustments in dealing with possible adverse events (Schreurs et al 1993), which has an effect on the amount of stress experienced (Ersan et al 2017). Specific coping styles (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has found that both academic and clinical workload were a significant source of stress for students. 1,6,11 Entry requirements for undergraduate courses include science prerequisites, top academic results (Queensland overall position "OP" one or equivalent grade point average), and very high aptitude test results on the undergraduate medical admissions test (UMAT) or the graduate medical school admissions test (GAMSAT). With different entry requirements between universities, the type of students and cohorts are likely to vary.…”
mentioning
confidence: 99%